Turismo, patrimonio e innovación en el contexto actual - ZAVALA CORDERO, MAURICIO; Ferro Vidal, Luis Enrique (Universidad de Colima, 2025)
The processes of Tourist Research in present times are of a multidisciplinary nature, though on some occasions, they are not represented in a documented manner. In this journey of reflexive thinking, the reader is invited to appropriate material, intangible, and natural reality. This compilation has Tourism as main research interest of Tourism, to heritage, and to innovation that happen at present.